The Philosophical Anthropology of José Manzana - Gómez Miranda, Rafael (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The main focus and interest of José Manzana’s philosophical anthropology is centred on the human condition, the sense of man’s action, the possibility of knowledge… and all that refers to «vertical transcendence», towards the Absolute, which finally culminates in God. With his philosophical anthropology, Manzana aims to ground on a transcendental method of reflection the conditions of man and his different options as a human being. The objective of this author is to clarify human existence by identifying his moment of creation. The aforementioned reflection brings us to three main dimensions of the individual: the human being as an inquiring entity, his interpersonal dimension and his awakening to the Transcendental.
Keywords: anthropology; interpersonal relationship; the Absolute-God